A közigazgatás értékkötöttsége az alkotmányos jogállamban - Ádám, Antal (Tér és Társadalom, 1999)
Due to the increasing of the constitutional and other legal values (like the moral values put on legal status and religious, ethicoreligious, political, social, health, scientific, cultural, artistic, natural and built environmental values honoured by state) the influence of values on public administration is extending and become stronger in a large measure. Modern public administration has to watch continuously the traditional and recent values and their changes. It has to take considerately an contribute part in the enlargement, caring, treatment and enforcement of values with its specific tools of supervision, control, other authority, planning, organisation, information, encourage and penalty. To summarise all of that the influence of values on public administration in a constitutional state is extraordinarily large, powerful, different and continuously changing.